Prognostic value of soluble endoglin in patients with septic shock and severe COVID-19 - Tomášková, Veronika; Mýtniková, Alexandra; Hortová Kohoutková, Marcela; Mrkva, Ondřej; Skotáková, Monika; Šitina, Michal; Helánová, Kateřina; Frič, Jan; Pařenica, Jiří; Šrámek, Vladimír; Helán, Martin (Frontiers in Medicine, 2022)
Sepsis is a clinical syndrome characterized by a dysregulated response to infection. It represents a leading cause of mortality in ICU patients worldwide. Although sepsis is in the point of interest of research for several decades, its clinical management and patient survival are improving slowly. Monitoring of the biomarkers and their combinations could help in early diagnosis, estimation of prognosis and patient’s stratification and response to the treatment. Circulating soluble endoglin (sEng) is the cleaved extracellular part of transmembrane glycoprotein endoglin. As a biomarker, sEng has been tested in several pathologic conditions where its elevation was associated with endothelial dysfunction. In this study we have tested the ability of sEng to predict mortality and its correlation with other clinical characteristics in the cohort of septic shock patients (n=37) and patients with severe COVID-19 (n=40). In patients with COVID-19 sEng did not predict mortality or correlate with markers of organ dysfunction. In contrast, in septic shock the level of sEng was significantly higher in patients with early mortality (p=0.019; AUC=0.801). Moreover, sEng levels correlated with signs of circulatory failure (required dose of noradrenalin and lactate levels; p=0.002 and 0.016 respectively). The predominant clinical problem in patients with COVID-19 was ARDS, and although they often showed signs of other organ dysfunction, circulatory failure was exceptional. This potentially explains the difference between sEng levels in COVID-19 and septic shock. In conclusion, we have confirmed that sEng may reflect the extent of the circulatory failure in septic shock patients and thus could be potentially used for the early identification of patients with the highest degree of endothelial dysfunction who would benefit from endothelium-targeted individualized therapy.